2017
DOI: 10.1136/bjsports-2017-098362
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue injury in calf muscle tears and return to play: MRI correlation

Abstract: The integrity of the connective tissue can be used to estimate and guide the time to return to play in calf muscle tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…12,13 Specific injury characteristics warrant consideration, such as the injury site 14,15 as well as the presence and severity of connective tissue disruption. 13,16 These characteristics can be determined from MRI, hence it is possible that baseline MRI findings may provide some insight regarding differences in recovery time frames following CMSI. 13,15,16 Furthermore, clinical factors at baseline may explain some of the variation in the time taken to return to play (RTP), but the prognostic value of clinical factors for estimating recovery following CMSI requires further investigation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Specific injury characteristics warrant consideration, such as the injury site 14,15 as well as the presence and severity of connective tissue disruption. 13,16 These characteristics can be determined from MRI, hence it is possible that baseline MRI findings may provide some insight regarding differences in recovery time frames following CMSI. 13,15,16 Furthermore, clinical factors at baseline may explain some of the variation in the time taken to return to play (RTP), but the prognostic value of clinical factors for estimating recovery following CMSI requires further investigation.…”
mentioning
confidence: 99%
“…13,16 These characteristics can be determined from MRI, hence it is possible that baseline MRI findings may provide some insight regarding differences in recovery time frames following CMSI. 13,15,16 Furthermore, clinical factors at baseline may explain some of the variation in the time taken to return to play (RTP), but the prognostic value of clinical factors for estimating recovery following CMSI requires further investigation. 17 It is likely that intrinsic factors, such as strength, flexibility, and functional capacity, as well as extrinsic factors, such as the stage of the season, the mechanism of injury, and whether it is a first time injury or a re-injury, [17][18][19] play a role in the time that it takes to achieve recovery milestones and RTP following CMSI.…”
mentioning
confidence: 99%
“…​Prolonged​ return to play​ ​has also been reported​ ​in​​ intramuscular​ ​tendon injuries to the ​rectus​ ​femoris​, ​gastrocnemius​ ​and​ ​soleus muscles. 5 …”
mentioning
confidence: 99%
“…In a series of 100 calf injuries, Prakash et al 29 observed that interruption of the muscle connective tissue resulted in a longer recovery time and a longer RTP time than injuries that did not affect the central tendon of the soleus. Although no reported studies have focused only on injuries of the central tendon of the soleus, it seems likely that a central tendon injury with tendon gap ( Figure 7A) will have a more complex progression than an injury in which the connective structure is not damaged ( Figure 7B).…”
Section: Central Tendon Of the Soleusmentioning
confidence: 99%
“…In general, injuries affecting the tendon of the central MCJ entail a longer RTP time than those in the peripheral MCJ. 27,29 This rule also applies for the central tendon of the rectus femoris. 4,10 Posterior Aponeurosis of the Rectus Femoris According to Cross et al, 10 injuries in the posterior peripheral MCJ of the rectus femoris have a faster RTP than those in the central MCJ of the central tendon.…”
Section: Central Tendon Of the Soleusmentioning
confidence: 99%